Powerful Weblogs: Design And Semiotic Description - Nikos, Fahantidis; Ifigeneial, Vamvakidou; Antonis, Traoudas; Ilias, Michailidis; Lazaros, Papoutzis (The Turkish Online Journal of Design Art and Communication, 2012)
Blogs are a very important "tool" for professionals and individuals wishing to promote products, services, thoughts, ideas, news. It is one of the most important channels of communication which brings them into contact with a very important public figure, the internet. Creating a blog is not a simple process but a complex mixture of different points and signs. In the present work we make an effort to define well-known blogs using semiotics. Our research material consists of the 20 most visited blogs, according to the list appearing in the «Technorati» blog search tool. For the analysis of the visual material we use the Grammar of Visual Design by Kress G. & Van Leeuwen T. (1996), a methodology based on the theory of Systemic Functional Grammar, which is the main subject of Halliday M. (1994). More specifically, in order to understand the power of weblogs, we are searching for: a) the mechanisms of organization and reconstruction of reality (representations), b) the production of meanings or even new ideologies by words and images (discourse) and c) the precise form and structure, signifiers and absences. It seems that web-blogs are creating a timeless space regulated by a nameless founder where the bits of information given although pointing to a specific date are part of a virtual non-time continuum.
Keywords: Internet; Blogs; Semiotics; internet; Bloglar; Semiyoloji